Theoretical Design of Offgrid Renewable Energy System Pv For Centrifugal Pump Electricity Supply - Umayyah, Nissaeryn Zahro; Hatuwe, Azmain Noor; Lilipaly, Eka R. M. A. P. (Journal Mechanical Engineering, 2024)
ABSTRACTThe off-grid PV system is an alternative power generator as a replacement for the conventional system which is currently still used in production operations at petroleum companies in Indonesia. The application of this offgrid PV system can support oil production operations for companies whose production areas are in remote areas or are still not reached by the PLN network and can reduce the consumption of fossil fuels to run generators so as to reduce greenhouse gas emissions and as a step to utilize the potential of Indonesia's sunlight. This research was carried out using a theoretical study method, namely by processing data obtained from the field using equations obtained from supporting references. This research shows that to meet the electricity needs of a centrifugal pump that operates 5 times a day with one operation of 7.5 kW for 1 hour and the total daily need is multiplied by 2 to calculate cloudy days, 75 kwh of energy is needed a day. The results of the research show that 40 solar panels with a capacity of 450 Wp each installed in series are needed and 80 LIFEP04 batteries made in battery banks totaling 20 banks with 4 batteries each, and 4 5000W inverters so that they can produce 75kWh of power and meet daily load requirements. Key words: offgrid PV system, Centrifugal Pump, parallel series